Recontextualization of the Words "Distance" and "Distancing" During the Covid-19 Pandemic: English - Akbar Ghifari Abdullah (JELP Journal of English Language and Pedagogy, 2023)
COVID-19 is a plague that has become a pandemic for the world. Necessary, many researchers who conduct research to understand about COVID-19, both medical and other scientific disciplines such as language science. The purpose of this study is to find out whether there is a contextualization of the words DISTANCE and DISTANCING with SOCIAL kolokat. For this reason, the mixed method is used to obtain coherent results. The results of this study indicate that the T-score of DISTANCING 16.1 and DISTANCE -14. This shows that the word SOCIAL is more commonly used with the word DISTANCING in corpora. The second finding is a recontextualization of the word DISTANCING in the negative direction.